2019
DOI: 10.7717/peerj.6417
|View full text |Cite
|
Sign up to set email alerts
|

The detailed distribution of T cell subpopulations in immune-stable renal allograft recipients: a single center study

Abstract: BackgroundMost renal allograft recipients reach a stable immune state (neither rejection nor infection) after transplantation. However, the detailed distribution of overall T lymphocyte subsets in the peripheral blood of these immune-stable renal transplant recipients remains unclear. We aim to identify differences between this stable immune state and a healthy immune state.MethodsIn total, 103 recipients underwent renal transplantation from 2012 to 2016 and received regular follow-up in our clinic. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…End-stage renal disease (ESRD), the final stage of CKD, is associated with high levels of immune activation, poor responses to immunisation and high susceptibility to infection. 126 The fact that uraemia-associated changes in the cd repertoire are not effectively reversed upon transplantation suggests that transplant patients may exhibit long-term susceptibility to some infections, similar to HIV ART-treated patients. 124 They speculated that cd depletion likely occurred because of Fas-and LFA-1dependent apoptosis related to uraemia.…”
Section: Similarities With Other Chronic Inflammatory Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…End-stage renal disease (ESRD), the final stage of CKD, is associated with high levels of immune activation, poor responses to immunisation and high susceptibility to infection. 126 The fact that uraemia-associated changes in the cd repertoire are not effectively reversed upon transplantation suggests that transplant patients may exhibit long-term susceptibility to some infections, similar to HIV ART-treated patients. 124 They speculated that cd depletion likely occurred because of Fas-and LFA-1dependent apoptosis related to uraemia.…”
Section: Similarities With Other Chronic Inflammatory Diseasesmentioning
confidence: 99%
“…cd frequencies only partially normalise following kidney transplantation, with Vd2 frequencies remaining significantly lower than healthy controls. 126 The fact that uraemia-associated changes in the cd repertoire are not effectively reversed upon transplantation suggests that transplant patients may exhibit long-term susceptibility to some infections, similar to HIV ART-treated patients.…”
Section: Similarities With Other Chronic Inflammatory Diseasesmentioning
confidence: 99%
“…Our previous study suggested that compared with healthy controls (HC), renal transplant recipients with accommodation had reduced proportions of γδ and Vδ2 subsets, as well as CD27 + CD28 + subsets in both the CD4 + and CD8 + T-cell compartments, but the programmed cell death protein (PD) 1 + CD4 + and CD8 + T-cell subsets were increased. Additionally, an increased percentage of CD4 + effector memory T cells and a decreased fraction of CD8 + central memory T cells were found in the renal allograft recipients with accommodation ( Zhuang et al, 2019 ). We also reported that multiple subpopulations of B cells were altered in renal allograft recipients with accommodation, including reduced levels of regulatory B cells (Bregs) (CD38 high CD27 + CD24 + ), transitional B cells (IgM + CD38 high CD24 high ), and marginal zone (MZ) B cells but increased levels of IgD - CD27 + and CD38 low CD21 - B cells ( Zhuang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, 50 μ L of whole blood was stained with fluorescent antibodies for 15 minutes in the dark (room temperature). The specific steps have been described in the previous study [ 34 ]. All samples were analyzed using BD FACSDiva software.…”
Section: Methodsmentioning
confidence: 99%